A double‐metallic‐layered Huygens' surface for broadband and highly efficient beam refractions. Issue 5 (7th March 2016) - Wang, Zheng‐Bin; Xue, Manlin; Zhang, Huamei; Wu, Zhihang; Li, Bo
ABSTRACT: In this article, a double‐metallic‐layered Huygens' surface Huygens' surface that efficiently refracts normally incident electromagnetic waves at the telecommunication frequency of 25 GHz is reported. The phase gradient along the interface is controlled by a series of isotropic, nonresonant, spatial phase shifters with dimensions of 0.5 λ 0 × 0.5 λ 0, where λ 0 is the free‐space wavelength at 25 GHz. The electric and magnetic responses of the unit cells are controlled by metallic patterns etched on both sides of an ultrathin dielectric substrate (with thickness of 0.07 λ 0 ). These surface microstructures are shown to be able to fabricate high‐efficiency refract‐arrays, ultrathin, wideband focusing lenses. The full‐wave simulations demonstrate their excellent performances in manipulating electromagnetic wavefronts. The measured results for the fabricated refract‐array further show that it can refract normally incident waves to the predefined angle, and the peak value of the transmission efficiency approaches 76%. © 2016 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:449–455, 2016.